Pax Mongolica \ Pax Mongolorum - Ц., Шагдарсүрэн (Mongolian Studies, 2023)
The domestic and foreign policy of the Mongols has, from earliest times, privileged the establishment of peaceful living conditions, a clear example of which is the principle of tolerance for the language, religions and beliefs, and livelihoods and customs of the many peoples governed by the Mongols. Many foreign Mongolists have argued in recent years that the process of globalization, taken as a way of life and in terms of communication, began with the period of Chinggis Khaan, though the governing principles of each period are distinct. Contemporary globalization is clearly based on the principle of empires forcing their on languages, religions, culture, and ways of life onto smaller, weaker countries, leading to some forms of resistance. Yet the period of Chinggis Khaan was extremely different, being characterized by a commitment to live by way of Mongolian life, viewing language and writing tolerance, life tolerance or way of life tolerance, and religius tolerance as ensuring social peace and stability.